Critical success factors influencing the resilience of food and beverages SMEs in Malaysia - Yusuf, Yusni Munirah; Ab Rahman, Siti Maziah; Bustaman, Hasnun Anip (Journal of Islamic, Social, Economics and Development, 2025)
This paper represents a conceptual framework that explores the relationship between business performance which comprise of four (4) main elements that are financial performance, operational performance, strategic performance and customer-related performance on the resilience of food and beverages small and medium enterprise (SME) in Malaysia. In highly volatile and technological advancement in business nowadays has always opened an opportunity for new comers to enter the market, making it more competitive and fiercer. This study embarks on dynamic capabilities theory to explain how the three (3) elements in the theory could lead a business to enhance more their business performance and thus, serves as framework foundation for both academic research and practical implication for the future researcher.